APPLYING THE MAKE A MATCH LEARNING MODEL TO IMPROVE CIVICS LEARNING OUTCOMES ON THE IMPORTANCE OF DELIBERATION AMONG GRADE V STUDENTS AT BAITUL A’LA ISLAMIC ELEMENTARY SCHOOL - Fadiah Aura Andika (CV Grasta Glory, 2025)
This study aims to investigate the effectiveness of the Make A Match learning model in enhancing student learning outcomes in Civics Education (PKn), specifically on the topic “The Importance of Deliberation in My Life.” The background of this research is based on the low student motivation and learning outcomes often observed in Civics classes, caused by traditional, teacher-centered instructional approaches. To address this issue, an interactive and engaging model—Make A Match—was implemented, which encourages students to actively participate through a card-matching activity designed to reinforce key concepts in a fun and collaborative way. The research method used is a quasi-experimental design with a one-group pre-test and post-test. The sample consisted of 23 fifth-grade students from SD Islam Baitul A’la. Data collection was carried out using a multiple-choice test of 18 validated items administered before and after the intervention. The pre-test results showed a mean score of 44.70, indicating limited prior understanding. After the application of the Make A Match model, the post-test mean score increased significantly to 83.05. Hypothesis testing using the Z-test showed Zcount = 6.94, which is greater than Ztable = 1.64 at a significance level of 0.05, indicating a statistically significant improvement in learning outcomes. These findings support the conclusion that the Make A Match model is effective in improving students’ cognitive achievements in Civics Education. Additionally, it promotes collaboration, engagement, and enjoyment in learning. The model is recommended for broader application in elementary education to foster critical thinking, civic responsibility, and active classroom participation. t is recommended that future studies apply this model in different subjects and grade levels to explore its broader impact on active learning and civic competence.